Perumusan Blue Ocean Strategy Dalam Upaya Memenangkan Persaingan Bisnis (Studi Pada Barn Coffee Sukabumi) - Emilio Reggy Sanggra Djorghi; Erry Sunarya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The increasing number of Coffee Shops in Sukabumi City significantly continues to grow, making Barn Coffee required to survive and compete by determining the right strategy. Barn Coffee has implemented various strategies. In the last 3 years Barn Coffee has experienced a significant decline in profit. This study uses a qualitative descriptive method with participants being consumers who visit Barn Coffee and Nama Coffee as competitors of Barn Coffee. In the formulation of the initial strategy canvas using a scorecard approach that describes the position of Barn Coffee against its competitors. The results showed that in several factors Barn Coffee was superior to its competitors, such as taste and service. Meanwhile, on other factors such as price, sales promotion, interior and supporting facilities, Barn Coffee is still far behind compared to its competitors. there are several things Barn Coffee must do to get out of the red ocean trap and switch to the blue ocean using a blue ocean strategy. Among them are, increasing sales promotions, interior and supporting facilities as well as creating new product variants such as iced coffee strawberry, affogato with cheese, and iced coffee palm sugar. Keywords : Blue Ocean Strategy, Six Road Framework, Four-Step Framework, Red Ocean Traps